2009
DOI: 10.1111/j.1460-9568.2008.06564.x
|View full text |Cite
|
Sign up to set email alerts
|

A centrifugal pathway to the mouse accessory olfactory bulb from the medial amygdala conveys gender‐specific volatile pheromonal signals

Abstract: We previously found that female mice exhibited Fos responses in the accessory olfactory bulb (AOB) after exposure to volatile opposite-, but not same-sex, urinary odours. This effect was eliminated by lesioning the main olfactory epithelium, raising the possibility that the AOB receives information about gender via centrifugal inputs originating in the main olfactory system instead of from the vomeronasal organ. We asked which main olfactory forebrain targets send axonal projections to the AOB, and whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…Clues as to the circuit role of the feedback connections from the medial amygdala to the AOB were found by combining retrograde tracing with c-fos labeling after exposure to odors (Martel and Baum, 2009). A significant increase in fos-positive retrogradely-labeled neurons was seen in those mice (all female) which were exposed to male mouse urine volatiles; using other odors produced little or no increase.…”
Section: Other Inputs To the Aobmentioning
confidence: 98%
“…Clues as to the circuit role of the feedback connections from the medial amygdala to the AOB were found by combining retrograde tracing with c-fos labeling after exposure to odors (Martel and Baum, 2009). A significant increase in fos-positive retrogradely-labeled neurons was seen in those mice (all female) which were exposed to male mouse urine volatiles; using other odors produced little or no increase.…”
Section: Other Inputs To the Aobmentioning
confidence: 98%
“…Model7 pp: À 1214ðcol: fig: : NILÞ Moreover, many studies indicate that this part of the brain is also strongly involved in the integrative circuitry mediating pheromonal and reproductive functions (Baum, 2009;Kevetter and Winans, 1981;Martel and Baum, 2009;Morris et al, 2008;Segovia et al, 2006) as well as various aspects of its anatomy and physiology seem to be sexually dimorphic (Hamann, 2005;Fagergren and Hurd, 1999;King et al, 1999;Morris et al, 2008;Rollins and King, 2000;Równiak, 2013;Segovia et al, 2006;Swaab et al, 2003). An important role in the sexually dimorphic functions mediated by the amygdala and other brain structures may be played by cells which contain γ-aminobutyric acid (GABA).…”
Section: Bres : 44071mentioning
confidence: 98%
“…In addition, it has been recently suggested that the AOB receives backward connections from several forebrain sites including the bed nucleus of the accessory olfactory tract, the rostral portion of the medial amygdala (MeA), and the posteromedial cortical nucleus of the amygdala (PMCo). When exposed to male urinary volatiles, these connections show specific activation, suggesting that main olfactory-MeA-AOB signaling may motivate approach behavior to opposite-sex pheromonal signals that ensure successful reproduction [71].…”
Section: Convergence Between Main and Accessory Olfactory Pathwaysmentioning
confidence: 99%